Cơ chế tắt huỳnh quang của dipyrenyl calix[4]aren khi tạo phức với Fe3+ - Quang và cộng sự, Dương Tuấn (Vietnam Journal of Chemistry, 2014)
The investigations on fluorescence of dipyrenyl calix[4]arene in free state as well as of its Fe3+ complex have been carried out with changes in pH, temperature, solvent. The results show that dipyrenyl calix[4]arene exhibits monomer and excimer emissions depending on nature of solvent. Based on the way of fluorescence changes under different conditions, the fluorescence quenching of dipyrenyl calix[4]arene upon complexation of Fe3+ is attributed to the electron transfer from the excited pyrene to Fe3+ ion.